Job satisfaction and job performance : The moderating role of gender differences - Heng, Lee Kiang; Hana, Hamidi; Rusli, Ahmad (2011)
This study was conducted to examine the moderating effect of gender differences towards the relationship between job satisfaction and job performance. Although studies about relationship between job satisfaction and job performance have been conducted over the years, moderating role of gender differences has received less attention in job satisfaction models. With little empirical knowledge about these relationships, this area is crucial for further research hence the reason for conducting this study. The survey research method was used to gather 170 usable questionnaires from a sample of employees in a manufacturing factory in Muar. lohor. Over the past years, the characteristics of job satisfaction have been much highlighted. This study will be looking at the 5 important elements of job satisfaction as included in Model of Job Description Index POI). The variables being looked at in this study which fall under the job satisfaction construct are pay, promotion, supervision, work and co-workers. The dependent variable is job performance which is being looked at through employees' perception of their job performance. The moderator being studied is gender differences. This study looked at 5 direct effect hypotheses and 5 indirect effect hypotheses to test the moderating effect of gender differences. Pearson Correlation, Multiple regression and Hierarchical regression analyses were used in the study to test the hypotheses. The outcomes of hierarchical regressions show that the gender differences and job satisfaction had not increased job performance. Therefore, this result confirms that gender differences are not a moderator in the relationship between job satisfaction and job performance. This finding could be affected by corporate culture, ethnicity differences, qualification differences and racial differences rather than gender differences. Hence, diversity should be considered in the relationship and can be looked at further in future research. The implications of this study to theory and practice, conceptual and methodological limitations as well as directions for future research are discussed.